PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING(PBL) DI KELAS IV SDN 17 KAPENCONG KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Yuni mar (FKIP UMSB, 2017)
Social Studies (IPS) is one of the subjects given ranging from SD / MI / SDLB to college. IPS examines a set of events, facts, concepts, and generalizations relating to social issues. On the SD / MI social studies contain materials Geography, History, Sociology and Economics. Learning social studies will become a knowledge, skills, and understanding of the attitudes and values to students, if teachers are able to determine how best to convey the material contained in the Social Science subjects. And learning will work well if the teacher as facilitator and motivator for students not only to teach the monotony, but vary in methods, models, approaches and learning media bervarisi. Planning learning by using a model of Problem Based Learning (PBL) has been implemented in accordance with a predetermined plan, which has two cycles. In the first cycle carried out as much as 2 meetings and the second cycle executed as many as 1 x meeting. The results showed an increase in student learning outcomes of the first cycle of the first meeting, namely 70.8 to the second cycle is 90.4. Thus the research results show an increase in student learning outcomes is 19.6 with learning completeness percentage of 92%. Key words: student results, IPS, problem based learning methods